Exercise and Nutrition Strategies for Combating Sarcopenia and Type 2 Diabetes Mellitus in Older Adults - Dionysia Argyropoulou; Nikolaos D. Geladas; Tzortzis Nomikos; Vassilis Paschalis (Journal of Functional Morphology and Kinesiology, 2022)
Medical and technology development have drastically the improved quality of life and, consequently, life expectancy. Nevertheless, the more people who enter the third-age, the more geriatric syndromes expand in the elderly. Sarcopenia and Type 2 diabetes mellitus (T2DM) are common diseases among the elderly and the literature has extensively studied these two diseases separately. Recent evidence, however, revealed that there is a bidirectional relationship between sarcopenia and T2DM. The aims of the present review were: (1) to present diet and exercise interventions for the management of sarcopenia and T2DM and (2) identify which diet and exercise interventions can be used simultaneously in order to effectively deal with these two disorders. Exercise and a balanced diet are used as effective countermeasures for combating sarcopenia and T2DM in older adults based on their bidirectional relationship. Lifestyle changes such as exercise and a balanced diet seem to play an important role in the remission of the diseases. Results showed that chronic exercise can help towards glycemic regulation as well as decrease the incidence rate of muscle degradation, while diet interventions which focus on protein or amino acids seem to successfully treat both disorders. Despite the fact that there are limited studies that deal with both disorders, it seems that a combined exercise regime (aerobic and resistance) along with protein intake > 1gr/kg/d is the safest strategy to follow in order to manage sarcopenia and T2DM concurrently.